2021
DOI: 10.1149/2162-8777/abf2e0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of HfO2 Charge Trapping Layer Characteristics After UV Treatment

Abstract: The improvement in the charge storage characteristics in a non-volatile memory (NVM) device employing an ultraviolet (UV)-treated hafnium oxide (HfO2) layer as the charge-trapping layer is reported. X-ray photoelectron spectroscopy analysis was performed to characterize the Hf 4f and O 1s peaks. The defect densities corresponding to Hf and O after short-term UV treatment are 24.74% and 14.16%, respectively. The electrical characteristics, such as the interface trap density (Dit), dielectric constant, and flat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…The electron dispersive spectroscopy (EDS) line scans below the TEM images also indicate minimal atomic/interfacial changes. It has been demonstrated that CTM cells exhibit charge retention times over 10 years [92][93][94] . = 1.6, 6.2, 0.25, 29.8 pm, respectively.…”
Section: Charge Trap Memory Experimental Demonstrationmentioning
confidence: 99%
“…The electron dispersive spectroscopy (EDS) line scans below the TEM images also indicate minimal atomic/interfacial changes. It has been demonstrated that CTM cells exhibit charge retention times over 10 years [92][93][94] . = 1.6, 6.2, 0.25, 29.8 pm, respectively.…”
Section: Charge Trap Memory Experimental Demonstrationmentioning
confidence: 99%
“…For example, the charge storage characteristics could be significantly boosted by proper treatments, e.g., annealing steps, UV irradiation, etc. [18][19][20]. Doping/mixing with other elements was a very efficient way to modify the density and spatial and energy location of electrically active defects.…”
Section: Charge Trapping Layermentioning
confidence: 99%
“…However, there is a high possibility of charge leakage due to the small conduction band barrier at the Si 3 N 4 /SiO 2 interface. Therefore, extensive research is currently being conducted on high -k dielectrics such as the metal oxides (Ta 2 O 5 [ 1 ], TiO 2 [ 5 ], HfO 2 [ 6 ], ZrO 2 [ 7 ]) as charge trap layers, because of the higher conduction band barrier at the interface with SiO 2 compared to the Si 3 N 4 for better charge retention.…”
Section: Introductionmentioning
confidence: 99%